The combined effects of surface texture, flow patterns and water chemistry on corrosion mechanisms of stainless steel condenser tubes. (January 2020) - Abdul Jawwad, Abdul Kareem; Mohamed, I.K.
Highlights: Surface texture plays a major role in initiating under deposit corrosion (UDC). UDC morphology is dependent on water chemistry. Stagnant flow conditions associated with UDC may be caused by minor undetected manufacturing defects. UDC can be followed by flow accelerated corrosion (FAC) upon tube wall perforation. CFD can be successfully used to study both UDC and FAC. Abstract: Detailed failure analysis was carried out for a set of leaking vertical condenser tubes made from AISI 304L-type stainless steel. Experimental part of the analysis included non-destructive testing (eddy current testing and dye-penetrant testing), visual and stereoscopic examination, mechanical testing, chemical analysis, optical and scanning electron microscopy (SEM) and X-ray diffraction (XRD). The present failure was found to be a result of a sequence of several interrelated actions. Experimental evidence indicated the leaking to be caused by surface-breaking pitting resulting mainly from under deposit corrosion (UDC) mechanism. The observed UDC, however, was associated with the presence of distinct surface features promoting low local flow velocities and stagnation conditions. These features are believed to be the result of the specific inside diameter (ID) weld scarfing process. The present results also indicated that UDC was followed by flow accelerated corrosion (FAC) upon tube wall perforation. Computational fluid dynamics (CFD) was used to simulate water flow conditions inside the condenser tubes before and after perforation in order to evaluate the suggested failure sequence and the involved damage mechanisms. CFD results were found to be in strong support of the observed experimental evidence and the proposed failure mechanisms. Finally, the three interacting factors, i.e.; surface texture, flow conditions and water chemistry, are discussed in terms of their effects in leading to the observed final failure and forming its distinct morphology.